2016
DOI: 10.1111/aor.12671
|View full text |Cite
|
Sign up to set email alerts
|

Bilaminar Device of Poly(Lactic‐co‐Glycolic Acid)/Collagen Cultured With Adipose‐Derived Stem Cells for Dermal Regeneration

Abstract: Several materials are commercially available as substitutes for skin. However, new strategies are needed to improve the treatment of skin wounds. In this study, we developed and characterized a new device consisting of poly(lactic-co-glycolic acid) (PLGA) and collagen associated with mesenchymal stem cells derived from human adipose tissue. To develop the bilaminar device, we initially obtained a membrane of PLGA by dissolving the copolymer in chloroform and then produced a collagen type I scaffold by freeze-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These effects may be mediated by the immunomodulatory and angiogenic capacities of SVF and ASC, which lead to increased capillary density, enhanced re‐epithelialization, and increased granulation tissue (Fig. I) . ASC also reduce scar formation likely through inhibition of collagen synthesis in late phases of wound healing .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may be mediated by the immunomodulatory and angiogenic capacities of SVF and ASC, which lead to increased capillary density, enhanced re‐epithelialization, and increased granulation tissue (Fig. I) . ASC also reduce scar formation likely through inhibition of collagen synthesis in late phases of wound healing .…”
Section: Resultsmentioning
confidence: 99%
“…I) . ASC also reduce scar formation likely through inhibition of collagen synthesis in late phases of wound healing . Chae et al further explored the differences in effects between SVF and ASC and found that SVF led to faster wound healing .…”
Section: Resultsmentioning
confidence: 99%
“…Biomaterials are commonly used in regenerative medicine to structure failing organs or tissue, as a scaffold, or to deliver cells or molecules, as vectors. PLGA polymers, for instance, are already used with adipose stem cells in different contexts: dermal (Domingues et al, ), peripheral nerve (Schuh et al, ), muscle (Kim et al, ) and corneal (Ma, Bao, Cui, & Zou, ) regeneration, osteogenic differentiation (Awidi et al, ), and engineered urinary bladder smooth muscle (Jack et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ASCs have been widely explored for skin application given its common mesoderm layer origins. Biomaterial-delivered ASCs is a common approach, including stem cell delivery methods on extracellular matrix scaffolds, hydrogels, and biodegradable polymers [18][19][20][21][22]. In one study, development of an injectable, thermosensitive hydrogel was explored [22].…”
Section: Adipose-derived Mscsmentioning
confidence: 99%